Imperiority of the "bolonya" transformations in the technical education (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2006)
Problems of the high education in Ukraine, wich connected with Europe education process are discussed. Quality of training the radioelectronics specialist, wich are a guaranty of conquerable them in this field and of the ability for getting the professional job in Europe